New U-Pb SHRIMP zircon ages for pre-variscan orthogneisses from Portugal and their bearing on the evolution of the Ossa-Morena tectonic zone - Cordani,Umberto G. (2006)
New SHRIMP U-Pb zircon ages for the Portalegre and Alcáçovas orthogneisses document a complex pre- Variscan history for the Iberian basement in Portugal. The available geochemical and geochronological data for the Alcáçovas orthogneiss (ca. 540 Ma) tend to favor its involvement in a Cadomian orogenic event. This is consistent with the development of an active continental margin setting at the end of the Proterozoic and supports a Gondwanan provenance for the Iberian crust. On the other hand, the Ordovician emplacement age obtained for the magmatic precursors of the Portalegre orthogneisses (497±10 Ma) provides additional evidence for the occurrence of rift-related magmatic activity during the Lower Paleozoic.